A qualitative study on the influence of Mahathir’s rhetorical communication in Malaysia’s GE 14 political campaign - Janice, De Cruz; Lee, Ei Kei; Loh, Kah Heng; Kwok, Wilbur Kenneth Zoen Ting; Wong, Kah Wai (2020)
A transformational leader that have a strong rhetorical communication is able to influence the public for attitude and behavioural change. The purpose of this study is to explore how Tun Dr. Mahathir bin Mohamad’s rhetorical communication influence the voter’s decision making in Malaysia GE14 political campaign. Eight informants from different nature in experience of diverse cultures were selected to be our samples in conducting our research. This research will be able to contribute to the model of rhetorical communication for future leaders. Based on our data analysis and findings, two research objectives has been investigated: The characteristic of Mahathir’s rhetorical communication that influence voters’ decision making in Malaysia’s GE14 political campaign and Mahathir’s rhetorical communication influence on voters’ decision making in Malaysia’s GE14 political campaign. All results have been divided into four main themes which will be linked to the influence of Mahathir’s rhetorical communication in GE14. All data collected has stated to contribute to the body of knowledge for future use.